2000
DOI: 10.1046/j.1365-2699.2000.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Maps of Pleistocene sea levels in Southeast Asia: shorelines, river systems and time durations

Abstract: Aim Glaciation and deglaciation and the accompanying lowering and rising of sea levels during the late Pleistocene are known to have greatly affected land mass configurations in Southeast Asia. The objective of this report is to provide a series of maps that estimate the areas of exposed land in the Indo‐Australian region during periods of the Pleistocene when sea levels were below present day levels. Location The maps presented here cover tropical Southeast Asia and Austral‐Asia. The east–west coverage extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,604
1
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,681 publications
(1,657 citation statements)
references
References 18 publications
36
1,604
1
16
Order By: Relevance
“…However, it is important 597 to consider the context at the time these species were evolving. The Gulf of Thailand has a 598 maximum depth of 80m, and Voris (2000) showed that for c. (Fig. 5a, b, & c and Fig.…”
Section: Non-spatial and Spatial Bayesian Mcmc Clustering Analyses 556mentioning
confidence: 91%
“…However, it is important 597 to consider the context at the time these species were evolving. The Gulf of Thailand has a 598 maximum depth of 80m, and Voris (2000) showed that for c. (Fig. 5a, b, & c and Fig.…”
Section: Non-spatial and Spatial Bayesian Mcmc Clustering Analyses 556mentioning
confidence: 91%
“…Lighter color land areas are more than 1000 m above sea level. The black lines show the maximum exposure of land during the Last Glacial Maximum (LGM) around 18,000 years ago when sea levels were 120 m below their current level (after Voris, 2000). The dashed line shows the contour line of exposed land when sea levels were around 40 m below current.…”
Section: Methodsmentioning
confidence: 99%
“…These connections lasted for tens of thousands of years, and the islands last became isolated only 10,000-12,000 years ago when sea level rose to less than 50 m below present levels (Voris, 2000;Hanebuth et al, 2000). Sea level remained below À50 m for approximately 40% of the time in the last 250,000 years (Voris, 2000), so the islands were not nearly as isolated from one another and the mainland as they are at present.…”
Section: Introductionmentioning
confidence: 99%
“…25 Archeological findings in the Massim are scant 26 and there is currently no evidence of long-term human occupation before 2 kya. 27,28 Given the lower sea levels during the Pleistocene, many of the current Massim islands may have been connected by land bridges, 29 potentially facilitating human migration between them. The languages spoken in the Massim belong to the Papuan Tip cluster within the Western Oceanic branch of the Austronesian language family, 30 with the exception of Rossel Island, the easternmost island of the Louisiade Archipelago, where a non-Austronesian (Papuan) language is spoken.…”
Section: Introductionmentioning
confidence: 99%